PENGEMBANGAN SISTEM APLIKASI UNTUK PELAPORAN DAN PEMANTAUAN KEBERSIHAN PEKERJA CLEANING SERVICE BERBASIS ANDROID (STUDI KASUS: PT. ISS INDONESIA BINTARO) - Alif Aulia Harun; Munaldi Munaldi (Informatika: Jurnal Teknik Informatika dan Multimedia, 2026)
This research was based on PT. ISS Indonesia Bintaro's need to improve the efficiency of cleanliness reporting and monitoring, which was previously conducted via WhatsApp. Frequently encountered problems included scattered reports, late verification, and a lack of evidence and documentation of work. Based on theoretical analysis of information systems, Android-based mobile applications, the Agile Scrum methodology, and several related studies, this research resulted in a comprehensive cleanliness reporting and monitoring application. Research techniques included data collection through observation, interviews, and a literature review, followed by UML design, database design, and application implementation using Flutter. Development iterations were guided by the Agile Scrum framework, allowing features to be tailored to meet user needs in the field. The results showed that the application facilitated the reporting process by allowing users to upload before-and-after photos, record locations, and enter work details in real time. Through a digital dashboard, supervisors could inspect, track work progress, and provide direct feedback. Black-box testing and user feedback demonstrated that the program ran as planned and helped improve work efficiency and monitoring quality. In essence, this program is an effective digital tool for improving reporting accuracy, transparency, and collaboration between supervisors and cleaning staff.